Synthesis of Cytokinins via Enzymatic Arsenolysis of Purine Nucleosides. Issue 1 (9th October 2018) - Oslovsky, Vladimir E.; Drenichev, Mikhail S.; Alexeev, Cyril S.; Solyev, Pavel N.; Esipov, Roman S.; Mikhailov, Sergey N.
Abstract: This unit describes an effective method for the preparation of natural cytokinins and their synthetic derivatives based on enzymatic cleavage of the N ‐glycosidic bond of N 6 ‐substituted adenosine or O 6 ‐substituted inosine derivatives in the presence of purine nucleoside phosphorylase (PNP) and Na2 HAsO4 . The arsenolysis reaction is irreversible due to the hydrolysis of the resulting α‐D ‐ribose‐1‐arsenate. As a result, the desired products are formed in near‐quantitative yields, as indicated by high‐performance liquid chromatography (HPLC) analysis, and can easily be isolated. In the strategy used here, the ribose residue acts as a protective group. © 2018 by John Wiley & Sons, Inc.